Enforcement of Regional Regulations on Local Taxes and Regional Levies by the Civil Service Police Unit (Satpol PP) of Asahan Regency North Sumatra Province - Abdul Wahab; Kanz Yafi Muhammad (Yayasan Hisnul Muslim Lombok, 2025)
This study aims to analyze the enforcement of Regional Regulation Number 10 of 2023 concerning Regional Taxes and Levies by the Civil Service Police Unit (Satpol PP) of Asahan Regency, particularly in the arts and entertainment services sector. Arts and entertainment taxes are a significant source of local revenue (PAD) to support regional development. However, the realization of tax revenue in this sector has not met the targeted goals. This research uses a qualitative descriptive method with a case study approach. Data were collected through interviews, observations, and documentation involving Satpol PP officers and local community members. The findings indicate that enforcement efforts face several challenges, both internal—such as limited human resources, facilities, and budget—and external, such as low awareness and compliance among taxpayers. Satpol PP’s efforts include public outreach, issuing warnings, conducting inspections, and closing businesses that violate the regulation. However, these efforts have not yet achieved optimal effectiveness. Therefore, improved inter-agency coordination, capacity building, and a more comprehensive enforcement strategy are required to increase tax compliance, achieve revenue targets, and maintain the quality of public services.